Glass in architecture from the pre- to the post-industrial era production, use and conservation - Wolf, Sophie; Hindelang, Laura; Giese, Francine; Krauter, Anne (Arts du verre/Glass art/Glaskunst, 2024)
Glass is one of the most fascinating and versatile building materials in architectural history. The new insights into glass in architecture are the result of research at the intersection of glass production, construction technology and building culture. Coming from a variety of disciplines, the contributions bridge the divide between natural sciences, humanities and the preservation and restoration of cultural heritage. They explore the crucial role of flat glass in shaping architecture, particularly since the 18th century, and discuss the in-situ restoration of historic windows and glass façades and the importance of preserving this fragile heritage. The topics range from the manufacture of sheet glass in pre-industrial times to the possibilities of repair and reusability of insulating glazing. With contributions in English, German and French A multi-disciplinary survey of the history of the production and use of flat glass From the Roman times to the present day New insights on sheet glass as building material and cultural heritage.